IMPACT OF INITIAL RENAL INVOLVEMENT AND BENCE JONES PROTEINS IN THE URINE ON OVERALL SURVIVAL OF PATIENTS WITH MULTIPLE MYELOMA - Krstevska Balkanov, Svetlana; Trajkova, Sanja; Pivkova Veljanovska, Aleksandra; Spasovski, Dejan; Ridova, Nevenka; Kalcev, Goce; Panovska Stavridis, Irina (Macedonian Association of Anatomists, 2022)
Multiple myeloma (MM) is a cancer of plasma cells with a frequency of around 50 cases per million population (pmp)/year. This retrospective study was conducted at the University Clinic for Hematology in Skopje, North Macedonia, in the period between January 2009 and December 2019. The cohort group was consisted of 296 recently diagnosed patients with MM. According to the results of our study, in 47% of patients who did not have renal involvement (RI), the survival rate was more than 60 months. On the other side, the survival percentage in those patients who had ARI (acute renal impairment) was 9% and in those who had CRI (chronic renal impairment) only 10%. Forty percent of patients with a negative Bence Jones proteinuria survived more than 60 months. Besides, only 20% of patients with a positive Bence Jones proteinuria survived more than 60 months. Nowadays, bortezomib is generally used as a first-line drug in the treatment of MM in patients with serious RI. In conclusion, there are various research questions that can differentiate the treatment of patients with MM and RI in the near future.
Keywords: multiple myeloma; overall survival; renal involvement; BJP; impact